Implementing Namaste Care in nursing care homes for people with advanced dementia: a systematically constructed review with framework synthesis - Serena Salvi; Nancy Preston; Nicola Cornally; Catherine Walshe; on behalf of the In-Touch Consortium (BMC Geriatrics)
Abstract Background Namaste Care is an intervention designed to improve the quality of life for people with advanced dementia by providing individualised stimulation and personalised activities in a group setting. Current evidence indicates there may be benefits from this intervention, but there is a need to explore the practical realities of its implementation, including potential barriers, enablers, and how it is delivered within the context of nursing care homes. Objective To systematically assess the factors involved in implementing Namaste Care for people with advanced dementia in nursing care homes. To provide pragmatic suggestions on how Namaste Care can be delivered in the context of nursing care homes. Design Systematically constructed review using framework synthesis. Data sources Comprehensive searches were conducted in Medline, CINAHL, and PsycINFO databases for studies published between 2018 and 2024. Search concepts included “Namaste Care,” “advanced dementia,” and related terms. Review methods Studies were included if they focused on the use of Namaste Care for people with advanced dementia in nursing care homes. Data extraction and quality assessment were performed by two independent researchers using standardised forms and critical appraisal tools. A framework synthesis of the results was conducted, which involves systematically combining qualitative and quantitative data within a structured analytical framework to identify overarching themes and insights. Findings Twenty-five studies met the inclusion criteria. Key themes identified were: (1) Frequency and duration of Namaste sessions. (2) Namaste Care environment and personalisation of care. (3) Staff engagement and training needs. (4) Involvement of family members and volunteers. Conclusions Implementing Namaste Care in nursing care homes presents various challenges but also significant opportunities for enhancing the quality of life for residents with advanced dementia. Addressing key themes such as the frequency and duration of sessions, the environment and personalisation of care, staff engagement and training needs, and the involvement of family members and volunteers is crucial. Specifically, providing tailored training programmes for staff, creating dedicated Namaste Care spaces, and encouraging active family and volunteer participation can facilitate effective integration. By incorporating these pragmatic recommendations, Namaste Care can be sustainably integrated into daily care routines, leading to improved resident well-being, reduced behavioural symptoms, and enhanced caregiver-resident interactions.